Answer:
Step-by-step explanation:
6) Convert mixed fraction to improper fraction and then plugin the values in the formula.
b) 10 cubic yard is less than 11 2/3 cubic yard. So, it will fit in the wood shed.
7) Right side rectangular prism:
l = 16 in
w = 5 in
h = 20 - 14 = 6 in
Volume 1 = 16 * 5 * 6 = 480 cubic inches
Left side rectangular prism:
l = 9 in
w = 5 in
h =14 in
Volume 2 = 9 * 5 * 14 = 630 cubic in
Volume of composite solid = 480 + 630 = 1110 cubic inches
If you need to solve this equation you can multiply the both side of equation on (-1). Like that
<span>2 = (-x);
-1·2 = (-1)·(-x)
if you multiply negative and </span><span>positive </span>you'll have negative,
if you multiply negative and <span>negative you'll have </span><span><span>positive. So
</span>
</span>-2 = x. or
x = -2.
The answer is -2.
Well,
Emily received $40.00 and then withdrew $40.00. The final amount would be zero.
Jacoby climbed 782 feet to get to his campsite, and then descended 782 feet to get back to his car. His final change is zero.
The Eagles mad two points, but then the Bulldogs evened it out with another two points. The difference between the two scores would be the same.
Marcus ends up going down more than he goes up, so this is not a correct option.
The Ravens scored two points, but at the end the Raiders scored an additional 5 points, which set both teams to the same score.
Since there are an equal number of protons and electrons, and the protons have the same (but opposite) amount of charge as the electrons, the charges cancel each other out, leaving the atom with a neutral overall charge (0).
Well, we know perimeter is just adding all the lengths together.
And we already know 2 of the lengths, so we know the rest. 11 1/2 is the same as the opposite side, and 6 1/3 is the same as the opposite side.
So the sides are 6 1/3, 6 1/3, 11 1/2, 11 1/2.
Add them up:
6 1/3 + 6 1/3 + 11 1/2 + 11 1/2.
Improper fractions:
19/3 + 19/3 + 23/2 + 23/2.
Common denominator, (6):
38/6 + 38/6 + 69/6 + 69/6 = 214/6.
Simplify:
214/6 = 35 2/3
Answer:
4^4= 4^-1(3r+2)
4^4= 4^(-3r-2)
-3r-2 = 4
-3r= 6
r= -2
-
Step-by-step explanation: